Green Accounting Practices and Firm Performance: A Meta-Analysis - Maryanti, Istinganah Eni (HM Publisher, 2025)
This meta-analysis investigates the relationship between green accounting practices (GAP) and firm performance. While prior studies have explored this link, the results remain inconclusive. This study aims to provide a comprehensive and robust analysis of the impact of GAP on firm performance by synthesizing findings from various empirical studies. A systematic literature review was conducted using Scopus and Web of Science databases, identifying 10 relevant studies published between 2013 and 2024. These studies employed diverse methodologies and performance measures. We used a random-effects model to estimate the overall effect size and explored potential moderators influencing the relationship. The meta-analysis revealed a significant positive relationship between GAP and firm performance. Specifically, firms that adopted GAP exhibited improved financial performance, as measured by return on assets, return on equity, and Tobin's Q. Furthermore, the analysis identified industry type and the stringency of environmental regulations as significant moderators. This study provides compelling evidence that GAP contribute to enhanced firm performance. These findings have important implications for managers, policymakers, and investors, highlighting the potential benefits of incorporating environmental considerations into accounting practices.